Ochratoxin A cytotoxicity on Madin–Darby canine kidney cells in the presence of alpha‐tocopherol: Effects on cell viability and tight junctions. Issue 1 (1st March 2017) - Fusi, E.; Giromini, C.; Rebucci, R.; Pinotti, L.; Caprarulo, V.; Cheli, F.; Vitari, F.; Domeneghini, C.; Baldi, A.
Summary: Ochratoxin A (OTA) is a potent nephrotoxic fungi metabolite that affects animal and human health. At the cellular level, OTA is able to alter functions and viability by several mechanisms of action. Several strategies to counteract its toxicity have been studied. We investigated the role of α‐tocopherol in counteracting OTA oxidative damage in Madin–Darby canine kidney (MDCK) cells by pre‐incubating the cells for 3 hr with the antioxidant (1 nm, 10 μm ) and then adding OTA (0–1.2 μg/ml) for the following 24 hr. Cell viability, lactate dehydrogenase (LDH) release, TUNEL staining and occludin and Zo1 localization by immunofluorescence were determined. Here, 1 nm α‐tocopherol was shown to significantly reduce ( p < .05) the cytotoxicity, LDH release and apoptotic rate induced by OTA. The presence of the antioxidant at the same concentration maintained the localization of occludin and Zo1 in the rim of the MDCK cells after the 24‐hr OTA exposure. These results indicate that a low concentration of α‐tocopherol could block OTA toxicity, supporting its defensive role in the cellular membrane.